Evaluation of marine fuel supply system state based on AEC model - Yongjiu ZOU; Taili DU; Xingjia JIANG; Yuewen ZHANG (Zhongguo Jianchuan Yanjiu, 2021)
ObjectivesIn view of the development demand of intelligent engine room of ships, in order to uncover the potential failure factors of equipment in advance, a new AEC health state evaluation model suitable for the ship's system and equipment is proposed.Methods This model combines the improved analytic hierarchy process (AHP) and entropy weight method (EWM) to form a combined weight method to determine the comprehensive weight of each evaluation index, and then the cloud gravity center evaluation method (CGCEM) is used to evaluate the health status of the research object based on the weight of each evaluation index.ResultsThe proposed model is verified by the actual operation data of the fuel supply system on the ship, and the calculation results show that the weighted deviation degree of the actual operation data is 0.181 5, which belongs to the interval (0, 0.33) and is in a healthy state, which is consistent with the facts.Conclusions It indicates that the AEC evaluation model can accurately evaluate the health status of the fuel supply system and has certain practical application values in the intelligent ship status evaluation and maintenance decision-making .